Plenary Panel: The Rudder that Sails the Ship: Exploring Policy Responses (PLA Inside Out: An International Journal on Theory, Research and Practice in Prior Learning Assessment, 2025)
The focus of this plenary panel was on policy at the local, national, and international levels, the goals and principles underlying those policies, and the often-complex relationships between policy and VPL practices.